AKIBAT HUKUM BAGI PERSEROAN PERORANGAN YANG SUDAH TIDAK MASUK KRITERIA USAHA MIKRO DAN KECIL TIDAK MENGUBAH STATUSNYA MENJADI PERSEROAN PERSEKUTUAN MODAL - P, Christoforus Ryandra (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Research shows that Individual Companies are required to change their status to Capital Partnership Companies if they are no longer included in the Micro and Small Business Criteria regulated in Article 109 number 5 of Law Number 6 of 2023 concerning Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 Concerning Job Creation Becoming Law. which adds the provisions of Article 153 H of Law number 40 of 2007 concerning Limited Liability Companies, but has not yet been explicitly regulated regarding sanctions if an Individual Company does not carry out these Requirements, so that legal compliance is not created